Conceptualizing spiritual resilience: A framework for student character formation in Islamic religious education - Mendy Harmoko; Ani Ulfiana Latifah; Aisatun Nafisa; Jakaria Umro (Eduvista: Journal of Education and Innovation, 2026)
Strengthening students' character through Islamic Religious Education has become increasingly important amid contemporary moral and spiritual challenges; however, studies integrating the concept of spiritual resilience with the perspective of Islamic education remain limited. This study aims to analyze the concept of spiritual resilience in Islamic Religious Education and its contribution to students' character formation. A qualitative approach employing a library research method was adopted through content analysis of relevant scholarly literature. The findings indicate that spiritual resilience is a multidimensional construct developed through the internalization of tazkiyat al-nafs, ṣabr, tawakkul, and shukr, which strengthens students' emotional stability, moral integrity, adaptive behavior, and personal responsibility. Furthermore, this study proposes a conceptual framework integrating resilience psychology with Islamic epistemology as a foundation for developing a more holistic approach to character education within Islamic Religious Education. Abstrak Penguatan karakter peserta didik melalui Pendidikan Agama Islam semakin penting di tengah berbagai tantangan moral dan spiritual pada era kontemporer, namun kajian yang mengintegrasikan konsep resiliensi spiritual dengan perspektif pendidikan Islam masih relatif terbatas. Penelitian ini bertujuan menganalisis konsep resiliensi spiritual dalam Pendidikan Agama Islam serta kontribusinya terhadap pembentukan karakter peserta didik. Penelitian menggunakan pendekatan kualitatif dengan metode library research melalui analisis isi terhadap berbagai literatur yang relevan. Hasil penelitian menunjukkan bahwa resiliensi spiritual merupakan konstruk multidimensional yang dibangun melalui internalisasi nilai tazkiyat al-nafs, ṣabr, tawakkul, dan shukr, sehingga mampu memperkuat stabilitas emosional, integritas moral, perilaku adaptif, serta tanggung jawab peserta didik. Selain itu, penelitian ini menghasilkan kerangka konseptual yang mengintegrasikan perspektif psikologi resiliensi dengan epistemologi Islam sebagai landasan pengembangan pendidikan karakter yang lebih holistik dalam Pendidikan Agama Islam.